Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin